Pengaruh Penambahan Bubuk Jahe Emprit (Zingiber officinale var. Amarum) Terhadap Karakteristik Teh Celup Herbal Daun Ciplukan (Physalis angulata L.) - Widiyana, I Gede; Yusa, Ni Made; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i01.p05, 2021)
This study aims to determine the effect of the addition of emprit ginger powder and the right addition to getting the best ciplukan leaf herbal characteristics. The design used in this study was a Completely Randomized Design with the treatment of the addition of emprit ginger powder consisting of 5 levels, namely 0%, 10%, 20%, 30%, and 40%. This study was repeated three times to obtain 15 experimental units. The data obtained were analyzed by analysis of variance and if the treatment had a significant effect it was followed by Duncan's Multiple Range (DMRT) test. The results showed that ciplukan leaf herbal tea with the addition of 20% emprit ginger powder was the best treatment with the criteria of water content value of 7.84%, total phenol 1.18 mgGAE/g, total flavonoid 0.56 mgQE/g, antioxidant activity 58.02%, IC 50 812.96 ppm, yellowish-brown color, somewhat distinctive flavor of ciplukan tea leaves and somewhat dislike, rather bitter taste, and overall rather dislike reception.